Location Modelling and the Localization of Portuguese Manufacturing Industries - Paulo Guimar\~aes; Octávio Figueiredo; Douglas Woodward (European Regional Science Association (ERSA), 2004)
The recent index proposed in Ellison & Glaeser (1997) is now well established as the preferred method for measuring localization of economic activity. We critically review this index and build on the McFadden's Random Utility (Profit) Maximization framework to develop an alternative measure that is more consistent with the theoretical construct underlying the original work of Ellison and Glaeser. Given that our method is regression based it goes beyond the descriptive nature of the EG index and allows us to evaluate how the localization measure behaves with changes in the systematic forces that drive firms' location decisions. JEL classification: C25, R12, R39
Keywords: C25; R12; R39; 330